2001
DOI: 10.4049/jimmunol.167.3.1728
|View full text |Cite
|
Sign up to set email alerts
|

Autoantigen Glycoprotein 70 Expression Is Regulated by a Single Locus, Which Acts as a Checkpoint for Pathogenic Anti-Glycoprotein 70 Autoantibody Production and Hence for the Corresponding Development of Severe Nephritis, in Lupus-Prone BXSB Mice1

Abstract: Retroviral envelope glycoprotein gp70 is present in the sera of immunologically normal and autoimmune-prone strains of mice. However, only lupus-prone mice spontaneously develop gp70-anti-gp70 immune complexes (gp70IC), and these have been implicated in the development of nephritis. We investigated the genetic factors that affect the production of both free serum gp70 and gp70IC in the lupus-prone BXSB mouse strain by analyzing (BXSB × (C57BL/10 × BXSB)F1)- and (C57BL/10 × (C57BL/10 × BXSB)F1)-backcrossed male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 31 publications
(35 reference statements)
5
34
0
Order By: Relevance
“…However, as described above, it is apparent that other genetic factors also contribute to the loss of tolerance to gp70. There seems to be a threshold level of serum gp70, ϳ1.1 g/ml, under which minimal gp70IC is produced, a phenomenon shown previously by Haywood et al (11) in BXSB ϫ C57BL/10 crosses. The presence of individuals that have high serum gp70 levels and low gp70IC levels indicate there are other genetic factors that drive the production of gp70IC, and that it is not solely reliant on high levels of serum gp70 Ag.…”
Section: Relationship Between Gp70 Ag and Anti-gp70icsmentioning
confidence: 60%
See 3 more Smart Citations
“…However, as described above, it is apparent that other genetic factors also contribute to the loss of tolerance to gp70. There seems to be a threshold level of serum gp70, ϳ1.1 g/ml, under which minimal gp70IC is produced, a phenomenon shown previously by Haywood et al (11) in BXSB ϫ C57BL/10 crosses. The presence of individuals that have high serum gp70 levels and low gp70IC levels indicate there are other genetic factors that drive the production of gp70IC, and that it is not solely reliant on high levels of serum gp70 Ag.…”
Section: Relationship Between Gp70 Ag and Anti-gp70icsmentioning
confidence: 60%
“…NZB and NZW share the Fv1 nr allele (28), which encodes a protein that is polymorphic, truncated, and functionally different compared with the product of the Fv1 b allele (28). A previous study in which linkage to gp70 was examined in a BXSB ϫ C57BL/10 cross demonstrated no linkage to the distal region of chromosome 4 (11). Based on genotype (Table V), we confirm that NZB and NZW were identical in sequence and polymorphic features, and carry the Fv1 nr allele.…”
Section: Proposed Mechanism Of Chromosome 4 Locusmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several normal strains have equally high levels of serum gp70, indicating that the gp70 autoantigen is not nephritogenic by itself. By studying the progeny of crosses of lupus-prone NZB, NZW and BXSB with B6 or B10 strains, we (5) and others (10,11) mapped a quantitative trait locus (QTL) on chromosome 13 at ϳ37 centiMorgans (cM) from the centromere that was strongly linked with basal levels of serum gp70. This locus mapped to a chromosomal location different from that of previously identified loci, Sgp1 linked to the H2 locus on chromosome 17 (12), and Sgp2 located at the telomeric end of chromosome 7 (13).…”
mentioning
confidence: 99%